Jaguarundi (Puma yagouaroundi) (Geoffroy, 1803) (Carnivora, Felidae) food habits in a mosaic of Atlantic Rainforest and eucalypt plantations of southeastern Brazil - Tófoli, C. F. [UNESP]; Rohe, F. [UNESP]; Setz, E. Z. F. (Instituto Internacional de Ecologia, 2009)
A dieta de uma população de jaguarundi (Puma yagouaroundi) (Geoffroy, 1803) (Carnivora, Felidae) foi estudada entre novembro de 2000 e novembro de 2001, em 24,9 km² de mosaico de Mata Atlântica secundária e reflorestamento de eucalipto na Serra de Paranapiacaba, São Paulo, Brasil. A análise das 26 amostras fecais e regurgitadas, obtidas em 570.1 km de percurso, indicou o consumo de 19 itens alimentares em um total de 74 ocorrências de presas. Pequenos mamíferos foram os itens mais frequentemente encontrados na dieta (42,5%), seguidos por aves (21%), répteis (14%) e mamíferos de tamanho médio (3%). A porcentagem de ocorrência (PO) sugere que a dieta concentra-se, principalmente, em pequenos roedores (30%) e aves (21%). Foi também registrada a predação sobre serpentes da família Viperidae. A amplitude de nicho alimentar padronizada (Bsta = 0,76) mostra uma dieta generalista, entretanto, os dados sugerem que o jaguarundi consome principalmente pequenos vertebrados (mamíferos, aves ou répteis), sobretudo, espécies terrestres.

Food habits of jaguarundi (Puma yagouaroundi) (Geoffroy, 1803) (Carnivora, Felidae) were studied between November 2000 and November 2001, in a 24.9 km² area of secondary Atlantic Rainforest and eucalypt plantation, in the Serra de Paranapiacaba, São Paulo State, Brazil. Analyses of 26 fecal and regurgitate samples, obtained over a stretch of 570.1 km, showed the consumption of 19 prey items and 74 prey occurrences. Small mammals were the most frequent food item (42.5%), followed by birds (21%), reptiles (14%) and medium-sized mammals (3%). The percent occurrence (PO) suggests that the diet consisted mainly of small rodents (30%) and birds (21%). We recorded for the first time the predation of Viperidae snakes by P. yagouaroundi. Although having a large list of items and range of dietary niche breadths (Bsta = 0.76), our data show that jaguarundi prey mainly on small vertebrates (mammals, birds or reptiles), and even in tall tropical forests or eucalypt plantations, it preys mostly on animals that come to, or live on, the ground.
Hábitos alimentares do jaguarundi (Puma yagouaroundi) (Carnivora, Felidae) em mosaico de Floresta Atlântica e reflorestamento de eucalipto no sudeste do Brasil
Keywords: dieta; hábitos alimentares; jaguarundi; carnívoros de médio-porte; análise fecal; diet; food habits; jaguarundi; medium-sized carnivores; scat analyses